Nasal Colonization of Staphylococcus Aureus Among Preclinical Medical Students: Implications as Future Sources of Infection in Hospitals - Handayani, Lidya; Susanto, Vincentia Amaranggana Zebada; Dewi, Desak Nyoman Surya Suameitria; Yuwono, Natalia; Siahaan, Salmon Charles P.T. (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2024)
Staphylococcus aureus, a prominent human pathogen causing a range of infections, often asymptomatically colonizes various anatomical sites, posing heightened risks to immunocompromised individuals. This study aimed to determine the prevalence of asymptomatic nasal carriage of S. aureus among pre-clinical medical students at Universitas Ciputra. Fifty-seven fifth-semester medical students participated voluntarily, providing informed consent. Nasal swabs were collected twice, ten months apart, and S. aureus was identified using standard culture methods. Descriptive statistics were used to analyze carriage prevalence and patterns. Results indicated that 17% of participants carried S. aureus in their nasal passages. Almost all participants (98%) exhibited mixed bacterial flora on nasal swabs, with only 2% showing S. aureus as the sole organism. Methicillin-resistant S. aureus (MRSA) was detected in 10% of S. aureus isolates. Among those sampled twice, 49% tested positive for S. aureus at least once, with 35% classified as intermittent carriers and 14% as persistent carriers. This study underscores a notable prevalence of asymptomatic S. aureus nasal carriage among pre-clinical medical students, highlighting their potential role as reservoirs for bacterial transmission in healthcare settings.